L’insectarium de l’histoire de l’art ou le pouvoir de fascination de la peinture (Hommage à Daniel Arasse) - Chantoury-Lacombe, Florence (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2009)
In this article, the author explores the way in which art historians, mostly French, have made a theoretical use of insects to analyze practices of painting and the modalities of the glance. Attention to painted flies in Renaissance painting or the modalities of vision specific to some insects such as stick insects has encouraged reflections on visuality and modes of representation. In the form of a tribute to art historian Daniel Arasse, the author reviews his interpretations, after Giorgio Vasari and Andre Chastel, of pictorial details such as the fly. In works of the Renaissance, as both Christ's symbol and macabre detail, the fly carries several meanings and Daniel Arasse brings to light the polysemy of these pictorial signs. In her analysis of fifteenth-century scenes of exorcism, the present author stresses the proximity of these small creatures, rendered in an illusory manner, with various embodiments of the devil expectorated by the possessed. This devil in motion is not a stable motif; like a pictorial collage, it condenses an amalgam of details of insects with sexual and phantasmagoric connotations. In her study of representations of insects, the author concentrates her attention on the fascinating power of these images.